2016
DOI: 10.1007/s10826-016-0377-x
|View full text |Cite
|
Sign up to set email alerts
|

Parents with Suicidal Behavior: Parenting is Not Always Protective

Abstract: Deaths by suicide and nonfatal suicide attempts are pervasive problems in the United States, especially among those of child-bearing age. Prior research has indicated that parenthood is a protective factor against suicide. However, no study has examined the reasons for why some parents attempt suicide. Questionnaires (n = 87) and follow-up interviews (n = 75) were completed with parents who recently attempted suicide and were recruited in the Emergency Department. Respondents reported family or relationship pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(40 reference statements)
0
10
0
2
Order By: Relevance
“…The relationship between children and people is a protective factor as well as a factor that moderates between maternal severe chronic depression with suicidal ideation in adolescents aged 16 years (Hammerton et al, 2016). Interaction between parents and family is a protective factor of suicide behavior, but family (parents) can also be a risk factor for suicide behavior in adolescents (Cerel, Frey, Maple, & Kinner, 2016; Lensch et al, 2018). Although peers relate to suicidal behavior, the effect of peer support is less influential compared with parent support (MacKin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between children and people is a protective factor as well as a factor that moderates between maternal severe chronic depression with suicidal ideation in adolescents aged 16 years (Hammerton et al, 2016). Interaction between parents and family is a protective factor of suicide behavior, but family (parents) can also be a risk factor for suicide behavior in adolescents (Cerel, Frey, Maple, & Kinner, 2016; Lensch et al, 2018). Although peers relate to suicidal behavior, the effect of peer support is less influential compared with parent support (MacKin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 68 were excluded as they pertained to bereavement support/intervention in parent’s suicide ( n = 2) [ 33 , 34 ], interventions for adolescents ( n = 8) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], transmission and risk of suicidal behavior and other problems ( n = 22) [ 1 , 11 , 12 , 16 , 17 , 19 , 25 , 28 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], other reasons ( n = 15) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], family member’s experiences ( n = 9) [ 3 , 4 , 5 , 72 , 73 ...…”
Section: Methodsmentioning
confidence: 99%
“…There are no prevalent figures of how many children are exposed to a parent’s suicide attempt annually. Cerel found that 23% of children with a parent being treated in the emergency department after attempting suicide had been present and witnessed the episode [ 1 ]. In a study of adverse childhood experiences, four percent of the 13,494 adults that answered a questionnaire reported a parental suicide attempt [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Cerel et al . ). According to several studies, violence is also associated with psychiatric conditions such as mixed anxiety–major depressive, adjustment, anxiety and post‐traumatic stress disorders (Fornés et al .…”
Section: Introductionmentioning
confidence: 97%